2018
DOI: 10.21101/cejph.a4817
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and physiological risks of shift work in nurses: a cross-sectional study

Abstract: Objectives: Many jobs are associated with psychological or social risk factors. Knowledge of occupational diseases is essential for adopting rational control measures. The aim was to study and describe frequent social, psychological and physiological risk factors for nurses. Methods: Psychological and social risks were evaluated in nurses with regular or irregular shifts. In addition, differences between nurses or nursing assistants were studied. The Copenhagen Psychosocial Questionnaire, Eating Attitudes Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
2
19
0
6
Order By: Relevance
“…Those working shifts had a lower exercise adherence than those working at regular times. Among nursing personnel, shift work is also associated with sleeping problems, fatigue, and lack of energy [72,73], which might compromise exercise adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Those working shifts had a lower exercise adherence than those working at regular times. Among nursing personnel, shift work is also associated with sleeping problems, fatigue, and lack of energy [72,73], which might compromise exercise adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Those working shifts had a lower exercise adherence than those working at regular times. Among nursing personnel, shift work is also associated with sleeping problems, fatigue, and lack of energy [68,69], which might compromise exercise adherence.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Age and weight have been shown to be parameters to be assessed for negative influences related to physical and psychological factors, such as eating behaviors, insomnia, mood and anxiety [ 38 ]. It has been observed that nursing work presents high job stress and psychosocial risks, increasing with work experience [ 38 ].…”
Section: Introductionmentioning
confidence: 99%